Aplikasi Rekomendasi Supplier Supermaket Greensmart dengan Metode Analytical Network Process - Aldo Vallian Sayoga Tanu Wijaya; Alexander Setiawan; Agustinus Noertjahyana (Jurnal Infra, 2020)
In Running of bussiness, supplier is one of the important components. Therefore, the right supplier selection will make the business process run smoothly. During this time the process carried out at the greensmart supermarket is still done manually. The manual process can lead to the selection of suppliers that are less appropriate for greensmart supermarkets. This can have a negative effect on greensmart supermarkets which can suffer from time and material losses.With these problems, a system is needed to help greensmart supermarket owners choose suppliers. This system will provide an alternative decision for greensmart supermarket owners in choosing suppliers for goods that are supplied by the package. For the method to be used is the analytical network process. This method was chosen because it can handle the problem of relations between sub criteria. This method works by calculating user input in the form of weight comparison and then processed to produce an eigen vector then entered into a matrix called unweighted supermatrix, then an unweighted supermatrix multiplication process will occur with a cluster matrix, a cluster matrix is a weight comparison of existing criteria then processed into an eigen vector and the final process is the process of calculating the limiting matrix which is the result of the appointment of the weighted supermatrix until the results of the same row then the results will be made into recommendations.For the results in this thesi it can be concluded that the program can produce effective results and is in accordance with the needs of the greensmart supermarkets. In addition, the ANP method can produce results that are quite effective but have a fairly difficult complexity.